The Implementation of Good Governance in Enhancing the Effectiveness of Civil Servant Empowerment in Pandeglang Regency - Dian Wahyu Danial; Dian Purnamasari Abidin; Muhamad Agus Saepullah (HK-Publishing, 2025)
This research is motivated by the importance of applying good governance principles to support effective and efficient government administration, specifically regarding the empowerment of State Civil Apparatus (ASN) at the Civil Service and Human Resources Development Agency (BKPSDM) of Pandeglang Regency. ASN empowerment is a crucial factor in enhancing the quality of public services; thus, applying good governance principles is essential to ensure that every program is executed transparently, accountably, effectively, and efficiently. This study aims to analyze the application of good governance principles regarding the effectiveness and efficiency of BKPSDM in its efforts to empower ASN in Pandeglang Regency. A qualitative approach with a descriptive method was employed. Informants were selected using purposive sampling, and data were collected through observation, interviews, and documentation. The data were then analyzed using the Miles and Huberman interactive model—comprising data reduction, data display, and conclusion drawing—with validity tested through source and technique triangulation. The results indicate that the implementation of good governance at BKPSDM Pandeglang Regency has proceeded quite well through competency development programs, information transparency, and accountability in activity execution. Regarding effectiveness, empowerment programs have supported the improvement of employee competence, although not all targets have been optimally achieved. Regarding efficiency, efforts to maximize the use of budgets and facilities have been made, yet constraints remain concerning human resources, budget limitations, and the utilization of information technology. The study concludes by emphasizing the need for improved coordination, strengthened apparatus capacity, optimized digital systems, and continuous evaluation. It is recommended that BKPSDM strengthen institutional synergy and optimize internal resources to support the implementation of good governance more effectively. Keywords: good governance, effectiveness, efficiency, ASN empowerment, BKPSDM